Mukti Ali's Thoughts On Multicultural Education And Its Relevance To Contemporary Islamic Education - Andika Septio Harahap; As'ad As'ad (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
This study aims to analyze Mukti Ali’s thoughts on multicultural education and their relevance to contemporary Islamic education in Indonesia. Mukti Ali's ideas, which emphasize the values of religious pluralism and interfaith dialogue, have the potential to serve as a vital foundation for developing a more inclusive, tolerant, and adaptive form of Islamic education in response to social and cultural diversity. This research is categorized as library research (Sugiyono, 2016). Data collection was based on a literature review, including Mukti Ali’s works, scholarly writings, research reports, internet sources, magazines, and other relevant literature aligned with the focus of this study. The literature review was then analyzed and presented in a structured review format. The study refers to two types of data sources (Ary, D., Jacobs, L. C., Sorensen, 2010). First, primary data were obtained from several of Mukti Ali's books, such as Religion in the Struggle of Contemporary Society, Interfaith Dialogue, The Intellectual Landscape of Modern Islam in Indonesia, among others. Second, secondary data were taken from various scholarly works (e.g., academic journals, theses, dissertations, etc.) that discuss Mukti Ali’s thoughts on multicultural education and their relevance to contemporary Islamic education. The results of the study show that, although Mukti Ali’s ideas are highly relevant to contemporary Islamic education, their application in the Islamic Religious Education (PAI) curriculum remains very limited. Some of the main challenges identified include the lack of teachers’ understanding of multicultural education, insufficient integration of pluralistic values into the curriculum, and cultural and social barriers within society that still lean toward exclusivity. Nevertheless, Mukti Ali's thoughts offer significant solutions in addressing radicalization and intolerance through a more moderate and diversity-respecting educational approach.